2009
DOI: 10.1089/neu.2009.0895
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Early Administration of Sertraline on Depressive Symptoms in the First Year after Traumatic Brain Injury

Abstract: The potential for sertraline administered in the first 3 months after moderate to severe traumatic brain injury (TBI) to decrease the incidence of depression in the first year after injury was assessed in a double-blinded randomized control trial. Subjects were enrolled an average of 21 days after injury (none >8 weeks) followed by oral administration of placebo (50 subjects) or sertraline 50 mg (49 subjects) for 3 months. Subjects were not depressed at the time of study initiation. Outcome was assessed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…The HAM-D has been used in depression trials among those with TBI. [32][33][34][35][36] Despite its frequent use, to date only 1 study has validated the 17-item HAM-D as a screen for MDD in a TBI sample. 37 The HAM-D had a sensitivity of 93% and specificity of 78% on the basis of a cut-point of 7.…”
Section: Hamilton Depression Rating Scalementioning
confidence: 99%
“…The HAM-D has been used in depression trials among those with TBI. [32][33][34][35][36] Despite its frequent use, to date only 1 study has validated the 17-item HAM-D as a screen for MDD in a TBI sample. 37 The HAM-D had a sensitivity of 93% and specificity of 78% on the basis of a cut-point of 7.…”
Section: Hamilton Depression Rating Scalementioning
confidence: 99%
“…Potential TBI pharmacotherapies were tested in 11 post-acute RCTs, with positive treatment effects reported in six studies, including for methylphenidate (Whyte et al, 2004; Willmott and Ponsford, 2009), CDP-choline (Calatayud Maldonado et al, 1991) and pyritinol (Kitamura, 1981). A trial of phenytoin and carbamazepine was negative (Smith et al, 1994), and sertraline, carbamazepine, rivsatigmine and modafinil were found to have no significant treatment effects (Banos et al, 2010; Jha et al, 2008; Novack et al, 2009; Tenovuo et al, 2009). …”
Section: Pathophysiology Classification and Clinical Management Of Tbimentioning
confidence: 99%
“…1,3,6 Depression is associated with adverse outcomes including greater physical disability, 2 unemployment, 7 functional dependence, 8 post-concussive symptoms, 8,9 lower quality of life, 2,9 poor psychosocial functioning and community participation, 2,4,10,11 and suicidal ideation. [12][13][14] Thus far, there is mixed evidence for the efficacy of telephone counseling or antidepressants to prevent [15][16][17] or treat patients with depression after TBI. [18][19][20] A major gap in our knowledge has to do with the course of depressive symptoms after TBI.…”
mentioning
confidence: 99%